Survival after subacute cardiac rupture. - Qureshi, S A (1982)
A 43-year-old man collapsed suddenly, with pericardial tamponade, seven weeks after an inferior myocardial infarction. Pericardiocentesis disclosed very heavily blood stained fluid. Left ventricular angiography 10 days later showed a left ventricular aneurysm. At operation a left ventricular false aneurysm was resected and the patient recovered uneventfully.